Identifikasi Variabel Risiko Kesehatan dan Keselamatan Kerja (K3) Pada Pembangunan Waron Hospital - Rufiyani Devi (Jurnal Vokasi Teknik Sipil, 2024)
During the construction period, there will be risks that do not rule out the possibility of occurring, such as occupational health and safety hazards, one of which is the occurrence of work accidents. Lack of discipline in the use of PPE can also trigger these risks, so that it can make it possible for construction construction to have a high risk of work accidents. The purpose of this study is to identify the variables of occupational accident risk that can occur in the construction of Waron Hospital. This study collects data with secondary data taken from literature books, journals, and the internet. The results of the study obtained 38 risk indicators that were reviewed based on work items, namely 6 work items, and 13 work activities. The description of the work activities is that there are 4 risks in soil excavation work, 1 risk in material lifting work, 2 risks in welding cutting work, 3 risks in the installation of reinforcing steel frames, 4 risks in casting, 4 risks in formwork installation, 3 risks in material lifting, 1 risk in the preparation and cutting process work, 3 risks in the installation of roof and ceiling coverings, 3 risks in wall and stucco installation work, 4 risks in ceramic installation work, 3 risks in water pipeline installation, and 3 risks in electrical installation.